Curricular Conundrum: The Jesuit Ratio studiorum and Mary Ward’s Attempts to Balance Latin, Prayer, and Lace - Brown, Laura Feitzinger (Journal of Jesuit studies, 2024)
The 1599 Jesuit Ratio Studiorum effectively organized its educational mission. Catholic Englishwoman Mary Ward (1585–1645) adapted the Ratio as she sought to build a new order for women based on the Jesuit rule and open Catholic schools for girls across Europe. Despite remarkable success, she faced increasing opposition from Jesuits and other leaders. Scholars have explored objections raised against her schools; however, little research addresses objections to teaching girls Latin. In this article, I argue that Ward’s attempts to teach Latin ran into subtle cultural complications because of gendered expectations regarding the language’s uses and abuses, conflicts over time devoted to prayer, and parental and societal expectations regarding young women’s acquisition of handwork skills. Exploring these complications helps illuminate not only Ward’s adaptation of the Jesuit approach to teaching but also nuances in her own spirituality, especially regarding the relationship between active and contemplative lives.